Engineered polyethylene terephthalate hydrolases: perspectives and limits - Kawai, Fusako; Iizuka, Ryo; Kawabata, Takeshi (Applied microbiology and biotechnology, 2024)
Polyethylene terephthalate (PET) is a major component of plastic waste. Enzymatic PET hydrolysis is the most ecofriendly recycling technology. The biorecycling of PET waste requires the complete depolymerization of PET to terephthalate and ethylene glycol. The history of enzymatic PET depolymerization has revealed two critical issues for the industrial depolymerization of PET: industrially available PET hydrolases and pretreatment of PET waste to make it susceptible to full enzymatic hydrolysis. As none of the wild-type enzymes can satisfy the requirements for industrialization, various mutational improvements have been performed, through classical technology to state-of-the-art computational/machine-learning technology. Recent engineering studies on PET hydrolases have brought a new insight that flexibility of the substrate-binding groove may improve the efficiency of PET hydrolysis while maintaining sufficient thermostability, although the previous studies focused only on enzymatic thermostability above the glass transition temperature of PET. Industrial biorecycling of PET waste is scheduled to be implemented, using micronized amorphous PET. Next stage must be the development of PET hydrolases that can efficiently degrade crystalline parts of PET and expansion of target PET materials, not only bottles but also textiles, packages, and microplastics. This review discusses the current status of PET hydrolases, their potential applications, and their profespectal goals. Key points • PET hydrolases must be thermophilic, but their operation must be below 70 °C • Classical and state-of-the-art engineering approaches are useful for PET hydrolases • Enzyme activity on crystalline PET is most expected for future PET biorecycling Graphical Abstract